(untitled) (Bangladesh Journal of Physics, 2023)
The discovery of infinite-layer nickelates opens up a new era of high-Tc superconductors. The nickelate compounds are almost isostructural to the high-Tc cuprates. Both cuprates and nickelates are insulators in the absence of self-doping and become superconducting upon doping the CuO2 and NiO2 planes, respectively. The mechanism of high-Tc superconductivity in correlated electronic systems will undoubtedly gain new insights from a verification of the similarities and differences between these oxides. In this brief report, we study the published electronic band structures of nickelates and cuprates in the undoped ground state. By comparing and contrasting the ground state electronic band structures of cuprates and nickelates, we have made an attempt to understand the common electronic features which can be important for the emergence of superconductivity upon carrier doping. Bangladesh Journal of Physics, 30(1), 1-11, June 2023